2016
DOI: 10.4038/sljch.v45i2.8117
|View full text |Cite
|
Sign up to set email alerts
|

Platelet profile and its correlation to paediatric patients with acute malaria in a tertiary care hospital

Abstract: Introduction: Few studies are available as regards status of platelets in malaria in paediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
2
0
0
Order By: Relevance
“…The study also observed that PDW 6-10 was more sensitive for PF than PV infection [ 34 ]. This is agreed by other researchers that PDW in the range of 6-10 was a more sensitive indicator for falciparum (82.6%) than vivax (69.5%) malaria [ 47 ].…”
Section: Platelet Indicessupporting
confidence: 88%
See 1 more Smart Citation
“…The study also observed that PDW 6-10 was more sensitive for PF than PV infection [ 34 ]. This is agreed by other researchers that PDW in the range of 6-10 was a more sensitive indicator for falciparum (82.6%) than vivax (69.5%) malaria [ 47 ].…”
Section: Platelet Indicessupporting
confidence: 88%
“…This is also supported by other studies that MPV > 8 fL showed significant sensitivity of 61.5% with low specificity of 41%. The study also observed that higher MPV (>8 fL) was a more sensitive indicator for PV infection than other plasmodium species, which is similar to a study conducted by Gurudutt and Deepak [ 16 , 34 , 47 ]. There was a strong inverse correlation between platelet counts and MPV.…”
Section: Platelet Indicessupporting
confidence: 87%